A SOCIOLINGUISTIC ANALYSIS OF CODE SWITCHING IN NESSIE JUDGE'S YOUTUBE VIDEOS - Zain, Jihan Fathinuriza (KLAUSA (Kajian Linguistik, Pembelajaran Bahasa, dan Sastra), 2025)
This study tries to identify the types and functions of English and Bahasa Indonesia code switching used by Nessie Judge in her YouTube videos. This research also reveals her identify as a bilingual YouTuber, as well as her capacity to communicate in both Bahasa Indonesia and English. The research methodology used in this study was a descriptive qualitative approach. The researcher selected five videos from the #Nerror YouTube video area and their transcriptions as data sources. To obtain data, the researcher watched the videos several times and took notes on the code-switching instances. The transcriptions were then saved in an Excel sheet document for easier analysis. Data analysis involved interpreting the transcribed data. The results present that types of code switching are tag switching, intra-sentential switching, inter-sentential switching, and additional type. Speech representation, situation switch, insistence, giving an emphasis, clarification, person specification, question shift, discourse maker, and others are the functions of code switching. Nessie Judge’s proficiency in English and Bahasa Indonesia is demonstrated by her vocabulary. She needs her bilingual (or multilingual) ability to work as an Indonesian YouTuber. Due to the variety of people, she uses two languages as her market.